Gender responsive value chain development and the conservation of native fruit trees through an inclusive learning process: a case study in Western Ghats, India - Lamers, H.; Hegde, N.; Hermanowicz, E.; Elias, Marlène (Bioversity International, 2017)
Bioversity International and LIFE Trust (a local NGO) conducted a sequence of participatory research activities in Kalagadde-Kanchigadde to improve incomes earned from forest resources and make insitu conservation activities more gender and socially inclusive.